Menimbang Kaidah Penafsiran Hermeneutika Al Quran dan Kaidah Tafsir dalam Proyek Tajdid - Vicky Izza El Rahma (STAI Syaichona Moh. Cholil Bangkalan, 2015)
This study examines the concept and also the application of tajdÄ«din Qurâ€™an hermeneutics initiated by Abdullah Saeed and the principles ofQurâ€™an interpretasion (qawaid al-tafsir) which is carried by M. QuraishShihab. The result of this study will represent how important the entry ofhermeneutics is to ulÅ«m al-qurâ€™Än that have become well-established tool toanalize and comprehend Qurâ€™an.